Language and Spelling Issues in the Activity of "Chigatoy Gurungi" Organization (Eurasian Research Bulletin, 2023)
The article provides brief information on the work carried out by modernists in the early 20th century on the issues of language and spelling, the activities of the members of the "Chigatoy Gurungi" organization, and the contribution of Abdurauf Fitrat to the development of the Uzbek language.